Pernicious anemia with unusual associations - C A Mansoor (Iraqi Journal of Hematology, 2022)
Pernicious anemia (PA) is an autoimmune disease due to vitamin B12 deficiency secondary to Intrinsic Factor deficiency. A 65-year-old man presented with left lower limb swelling and pain for one week. He had loss of appetite and fatigue for one month. Investigations showed lower limb deep vein thrombosis and bicytopenia. On further evaluation, he was found to have PA, duodenal carcinoids, and primary biliary cirrhosis. He was managed with heparin (followed by warfarin), parenteral Vitamin B12, and ursodeoxycholic acid. He was referred to the gastroenterology department for management of duodenal carcinoid. On follow-up his blood counts were normal. We present a patient with PA who had three unusual associations simultaneously at the time of presentation which was never reported in the literature previously, to the best of our knowledge.